Factors affecting learning and decision-making in the Iowa Gambling Task - Fernie, Gordon (2007)
Damasio's somatic marker hypothesis (SMH; Damasio, 1994, 1996) integrates emotion with rational decision-making using evidence drawn from neurology, neuroscience and performance on a now widely cited decision-making test developed to model real-life in a laboratory setting (the Iowa Gambling Task; Bechara, Damasio, Damasio and Anderson, 1994). The SMH posits a critical input from an embodied emotional system (somatic markers) in making decisions in choice situations. But Damasio's consideration of how the undamaged brain interacts with the body has some interesting and somewhat controversial implications in the context of modern psychological research on choice behaviour. In interpreting behaviour on the IGT in accordance with the SMH three central assumptions have been made: a) that somatic markers indicate the goodness or badness of alternatives and without them decision-making cannot become optimal, b) this somatic biasing or guidance can occur unconsciously or in the absence of explicit knowledge, and c) that the system operates so as to maximize or achieve the best outcome in the long-term. The Experiments described in this thesis have explored the validity of the second and third assumptions and found that they are not accurately reflected in behaviour on the IGT. The importance of information about the IGT in the instructions participants receive suggested that explicit knowledge about the task is a more critical factor than any somatic input. No evidence of a somatic influence prior to the emergence of explicit knowledge sufficient to guide behaviour was found. Instead there were indications that knowledge precedes somatic activity on the IGT. Novel manipulations of the reinforcement contingencies in individual decks also revealed that immediate outcomes of choices are an important determinant of subsequent behaviour. Selection does not solely depend on long-term outcomes.